2006
DOI: 10.1111/j.1099-0860.2005.00001.x
|View full text |Cite
|
Sign up to set email alerts
|

Everyday Experiences of Homeless Young People in Supported Accommodation Programmes in Australia

Abstract: This paper investigates young people's accounts of governance in their everyday lives within a Supported Accommodation Assistance Program (SAAP) in regional Australia. The SAAP is a joint Commonwealth and State/Territory programme for assisting people who are homeless or at risk of homelessness by providing transitional supported accommodation and support services. The paper provides accounts of how two young people, Monica and Brendan, make sense of their everyday lives in relation to how they make decisions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Similarly, Bae's (2009) study of children and teacher interaction in preschools in Norway found that participation correlates to how teachers follow children's initiatives, respond to children and take children's point of view. Danby, Farrell, Powell and Leiminer's (2004) research examining Australian children's decision making in their everyday lives suggests that time spent at school was governed more than was their time at home. Rather than child participation principles being embraced, children's lives at school are impacted upon increasingly by adultdetermined regulation and control .…”
Section: Impediments To Participation In Early Childhood Educationmentioning
confidence: 99%
“…Similarly, Bae's (2009) study of children and teacher interaction in preschools in Norway found that participation correlates to how teachers follow children's initiatives, respond to children and take children's point of view. Danby, Farrell, Powell and Leiminer's (2004) research examining Australian children's decision making in their everyday lives suggests that time spent at school was governed more than was their time at home. Rather than child participation principles being embraced, children's lives at school are impacted upon increasingly by adultdetermined regulation and control .…”
Section: Impediments To Participation In Early Childhood Educationmentioning
confidence: 99%
“…It recognises that children have the capacity to competently reflect and interpret the social worlds within which they exist and therefore argues that children should be afforded opportunities to participate in processes that affect their lives (Jenks, 1982). The value of doing so has been demonstrated in multiple research projects that focus on children who experience disadvantage (Davies and Wright, 2008; Redmond, 2008) and as service recipients (Aubrey, 2006; Danby and others, 2006; Farrell and others, 2002; Moore and others, 2008).…”
Section: Research Approachmentioning
confidence: 99%
“…The focus on young children's lives in home and school contexts gave rise to an Australian study of the lived experiences of 120 young children aged four to eight years, from the standpoint of the children themselves. The study examined children's everyday decision-making in home and school contexts Farrell 2004, 2005;Danby, Farrell, and Leiminer 2006). Somewhat surprisingly, the study revealed that young children focused on homework in their lives, such that it prompted the question: how does homework 'work' for young children in the context of their everyday lives?…”
Section: Introductionmentioning
confidence: 95%
“…The study drew upon theoretical understandings of children's active engagement and participation in their everyday lives (Corsaro 1997;Danby and Baker 1998;James, Jenks, and Prout 1998;Theobald, Danby, and Ailwood 2011;Waksler 1991) and children's competence in accounting for their experience (Danby and Farrell 2005;Danby, Farrell, and Leiminer 2006;Farrell and Danby 2007). That children's own accounts of their experience were sought, rather than those of adults, including parents and teachers (legitimate though they may be), aligns to the notion of children as 'competent interpreters of their everyday worlds' (Danby and Farrell 2004, 35).…”
Section: Introductionmentioning
confidence: 99%